Trace element compositions in clinopyroxene and plagioclase, and crystallization temperature estimated after Sun and Liang (2017) for Wadi Somerah, Oman - Dominik Mock; David Axford Neave; Samuel Müller; Dieter Garbe-Schönberg; Olivier Namur; Benoit Ildefonse; Jürgen Koepke (PANGAEA, 2020)
As largest and best-exposed paleo-fast-spread oceanic crust on land, the Samail ophiolite in the Sultanate of Oman represents an ideal natural laboratory for investigating processes at fast-spreading mid-ocean ridges. We studied a layered gabbro sequence from the middle of the plutonic crust showing dm-scale modal layering with olivine abundance gradually decreasing from layer base to top (Wadi Somerah, Sumail block). Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) was performed in order to obtain trace element contents and rare earth elements (REE) in particular. Analyses were performed at the Institut für Geowissenschaften (Christian-Albrechts-Universität zu Kiel, Germany) using a 193 nm ArF excimer laser ablation system (GeoLasPro HD, Coherent) coupled to an Agilent 7900s ICP-MS. Analyses were performed as point measurements with 16 Hz pulse rate, 18 Jcm-2 fluence and a crater diameter of 120 μm on plagioclase, and 10 Hz, 12 Jcm-2 and a crater diameter of 32 μm on clinopyroxene. Differences in core and rim compositions of clinopyroxene reveal significant zonation with higher REE contents in the rim. Crystallization temperatures calculated using the REE-thermometer of Sun and Liang (2017; doi:10.1007/s00410-016-1326-9) vary between 1230 and 1300°C.